Escritos sobre dramaturgia y teatro de títeres (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
O artigo discute o papel do dramaturgo e analisa diversos aspectos relativos à dramaturgia no Teatro de Bonecos e no Teatro de Objetos, tais como: a importância da ação e a economia de palavras; a escolha de materiais e objetos que colaboram na definição da dramaturgia; a metáfora como recurso; a indissociação entre construção do texto e encenação. Por fim, o estudo apresenta a síntese da última aula ministrada pelo autor na sua condição de professorde Dramaturgia na Escuela de Titiriteros del Teatro General San Martín, em Buenos Aires, no ano de 2001.Palavras-chave: Dramaturgia; teatro de títeres; teatro de objetos.Abstract: This article discusses the role of the playwright and analyses various factors related to dramaturgy in Puppet Theatre and the Theatre of Objects such as: the importance of action and the economy of words; the choice of materials and objects that collaborate in the definition of the dramaturgy; the metaphor as resource; and the inseparability between construction of text and staging. Finally, the study presents a synthesis of the final class given by the author as theatre professor at the Escuela de Titiriteros del Teatro General San Martín, in Buenos Aires, in 2001.Key-words: Dramaturgy; puppet theatre; theatre of objects.